Proceedings of the second Western Australian workshop on information systems research: WAWISR'99 - Lin, Chad; Pervan, Graham (McGraw Hill, 1999)
In modern organisations a large portion of senior management's time is now being spent on finding ways to measure the contribution of the organisation's IS/IT investments to business performance It has been shown that IS/IT investments in many organisations are huge and increasing rapidly every year and yet there is still a lack of understanding of the impact of the proper IS/IT investment evaluation processes and practices in these organisations. At the same time, the issue of expected and actual benefits realised from IS/IT investments has also generated a significant amount of debate in the IS/IT literature amongst the researchers and practitioners. This is as true in Australia as it is in the rest of the developed world. Thus, one can argue that a detailed program of research into the current practice and process of IS/IT investment evaluation in Australia is warranted. This paper reviews the progress made in research in the are and proposes a research program incorporating services, case studies and expert focus groups to assess current practice and to develop an approach, model or framework based on the fit between theory and practice of IS/IT investment evaluation by large Australian organisations.